(untitled) (Revista de Crítica Literaria Latinoamericana, 2011)
The symbolic language of chaos is the very foundation of El entenado by Juan José Saer. In its multiple meanings, the concept of chaos is incorporated into the novel at every level of the narration: from the story (the tribe rituals and life), to the narrator’s experience as a captive and witness, and finally to the novel itself. The language of chaos and its symbolisms provide the text with the poetic perception of the world that Saer seeks to achieve in his novels, and also constitute an organizational principle. These aspects link Saer’s novel with Borges’ poetic and philosophical world. This study analyzes this link between both authors by focusing on two central aspects: the literary text perceived as a writing of readings (rather than just a result of pure invention), and the use of the language of chaos in its different meanings.